2010
DOI: 10.1007/s10620-010-1333-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Black Cumin (Nigella sativa) Oil on TNBS-Induced Experimental Colitis in Rats

Abstract: BCO, by preventing inflammatory status in the blood, partly protected colonic tissue against experimental ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 57 publications
2
29
0
3
Order By: Relevance
“…Both are products of the lipid peroxidation process and presumably the result of ROS action (21,22). In the present study, MDA, a good indicator of the degree of lipid peroxidation, was increased in the colonic tissues of rats with acetic acid induction, indicating the presence of oxidative damage (23). Increased MDA content might have resulted from an increase in ROS as a result of oxidative stress in the rats after acetic acid administration (24).…”
Section: Discussionsupporting
confidence: 50%
“…Both are products of the lipid peroxidation process and presumably the result of ROS action (21,22). In the present study, MDA, a good indicator of the degree of lipid peroxidation, was increased in the colonic tissues of rats with acetic acid induction, indicating the presence of oxidative damage (23). Increased MDA content might have resulted from an increase in ROS as a result of oxidative stress in the rats after acetic acid administration (24).…”
Section: Discussionsupporting
confidence: 50%
“…Of the five citations for Nigella sativa, three were prescribed as adjuvant for hemorrhoid treatment. This was supported by a preclinical study in which the treatment with Nigella sativa oil reduced the proinflammatory cytokine levels in TNBS induced experimental colitis (Isik et al, 2010). Bites and stings by poisonous animals are a common problem for most of the villagers working in fields and forests (Amiguet et al, 2005).…”
Section: Illness Categories With High F Ic Valuesmentioning
confidence: 92%
“…TNBS induces diffuse colonic inflammation, which is characterized by increased leukocyte infiltration, edema, and ulceration [36]. It is very well reported that administration of TNBS is associated with predominant activation of Th1-mediated immune response manifested by dense infiltration of local CD4 + T cells.…”
Section: Chemical Induced Models Of Chronic Intestinal Inflammationmentioning
confidence: 99%